2007
DOI: 10.1007/s00246-007-9027-9
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Difficulties and Growth Delay in Children with Hypoplastic Left Heart Syndrome versus d-Transposition of the Great Arteries

Abstract: The objective of this study was to identify the incidence of feeding difficulties in infants with hypoplastic left heart syndrome (HLHS) and d-transposition of the great arteries (d-TGA). Congenital heart disease is a risk factor for growth failure. The etiologies include poor caloric intake, inability to utilize calories effectively, and increased metabolic demands. The goals of our study were to (1) identify feeding difficulties in infants with HLHS and d-TGA and (2) assess their growth in the first year of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
180
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(191 citation statements)
references
References 12 publications
8
180
2
1
Order By: Relevance
“…Thirty-two studies that satisfied the inclusion criteria were included in the analysis (Fig 1). OCEBM levels of evidence varied from level 3 (9 studies) [9][10][11][14][15][16]20,23,26 to level 4 (23 studies) [6][7][8]12,13,[17][18][19]21,22,24,25,[27][28][29][30][31][32][33][34][35][36][37] ( Table 1). Occurrence of UVFP, type of surgery, patient demographics, and vocal fold assessment are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-two studies that satisfied the inclusion criteria were included in the analysis (Fig 1). OCEBM levels of evidence varied from level 3 (9 studies) [9][10][11][14][15][16]20,23,26 to level 4 (23 studies) [6][7][8]12,13,[17][18][19]21,22,24,25,[27][28][29][30][31][32][33][34][35][36][37] ( Table 1). Occurrence of UVFP, type of surgery, patient demographics, and vocal fold assessment are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In another study comparing infants with hypoplastic left heart (HLHS) and transposition of great arteries (TGA), the time to achieving full caloric intake (at least 100 kcal/kg/day) for the HLHS group (24 8 11.9 days) was significantly longer than for the d-TGA group (12.0 8 11.2 days, p ! 0.001) [12] . In addition, infants with HLHS had a higher incidence of feeding-related complications (reflux disease, aspiration, poor suck/swallow) than those with d-TGA (48 vs. 4%, respectively; p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…A few previous studies have examined the incidence and clinical impact of gastro-intestinal morbidity among neonates with hypoplastic left heart following the first stage palliation [2,12] . Among 117 infants, gastrointestinal complications occurred in 48 (41%) and included 18% with NEC, 18% with home feeding tubes and 8% who required a prolonged hospital stay for nutritional support [2] .…”
Section: Discussionmentioning
confidence: 99%
“…1 Additionally, several studies have consistently reported that malnutrition, ranging from mild undernutrition to complete failure to thrive, 2 is a common cause of morbidity in children with CHD. [3][4][5] Multiple factors contribute to growth impairment and malnutrition in infants and children with CHD, such as prenatal and genetic factors, hypoxia and hemodynamic factors, such as congestive heart failure, inadequate nutritional intake, swallowing dysfunction, gastroesophageal reflux, immaturity of the gastrointestinal tract, a hypermetabolic state, and nutrient malabsorption, [6][7][8] as well as psychosocial and hormonal factors. 9,10 However, in medically partially underserved nations such as Indonesia, poor access to care leads to late presentation of patients with CHD and also contributes to malnutrition.…”
Section: Methodsmentioning
confidence: 99%